(untitled) (Libyan Journal of Ecological & Environmental Sciences and Technology, 2021)
The aims of the study was to assess the degree of contaminations of the Tobruk gulf by measuring the concentrations of chemical parameters (pH, DO, BOD5, COD, TN and TP) and heavy metals concentrations (Fe, Zn, Mn, Cu, Ni, Co, Pb, Cd and Cr). Samples collections from seven locations along Tobruk bay. Average concentrations of chemical parameters and heavy metals were compared with the permissible limits of (WHO) 2011 World Health Organization. The results showed that the average concentrations of chemical parameters at all stations were higher than the permissible limits of WHO. However, the heavy metals concentrations fluctuate between some metals were higher than the permissible limits, such as Cr, Fe, Mn, Ni, Co, Pb and Cd and other metals as Zn and Cu exhibit lower contents. The study proved that Tobruk commercial port and Sewage discharge tube as one of the main sources cause polluted in Tobruk bay